Regreening Asa: The Role of UMP KKN Students in Reforestation of Landslide-Affected Land in Pohkumbang Village Through the Griya Alas Program - Ningsih, Ica Purnawati; Huda, Rois Choiril; Mulyanah, Mulyanah; Khasanah, Siti Zahrotun; Sya’fira, Mudhia Amal; Salsabila, Intan Rizki; Izzuddin, Hilmy; Wardoyo, Vyomita Cahya; Kusumawati, Aan; Arrosyid, Farhan Indra Fata; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
The Griya Alas program was initiated by students of the Real Work Lecture (KKN) of the University of Muhammadiyah Purwokerto (UMP) in Pohkumbang Village, Kebumen, as an effort to reforestation of landslide-affected land as a strategic step to restore the ecosystem and increase the resilience of the community to disasters. This research aims to describe the resilience of the community to disasters. This study aims to describe the role of UMP KKN students in planning, implementation, and evaluation. The method used is qualitative descriptive with a Community Rural Participatory (CRP) approach, which involves village officials, community leaders, and residents of RW 05 Gemplo Hamlet. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed with Miles and Huberman’s interactive model. The results of the study showed the success of planting 72 mahogany tree seedlings on 25-45% sloped land that was prone to landslides. The selection of mahogany trees is based on the strength of the roots and resistance to slopes, so it effectively resists erosion. The active participation of the community is seen in all stages of the activity, strengthening the sense of ownership and ecological awareness. Reforestation provides ecological benefits (increasing vegetation cover, soil stability, water absorption), economic (potential non-timber forest products), and social benefits (strengthening mutual cooperation). Monitoring and evaluation ensure the sustainability of the program and open up opportunities for future development. The Griya Alas program has been proven to not only restore the physical environment, but also build collective awareness and village resilience to disasters.